The nurse consultant in mental health services: A national, mixed methods study of an advanced practice role. Issue 5 (12th July 2019) - Brimblecombe, Neil; Nolan, Fiona; Khoo, Mary‐Ellen; Culloty, Leon; O'Connor, Kate; McGregor‐Johnson, Lindsay
Accessible summary: What is known on the subject?: Internationally, systematic reviews have identified evidence of equal or improved clinical outcomes comparing advanced practitioner treatment with medical treatment as usual, across a range of specialities. Studies of nurse consultants in the United Kingdom have largely been non‐empirical. Most studies specifically related to nurse consultant roles in mental health services are case studies or reports of views on this role. What this paper adds to existing knowledge?: The study demonstrates that nurse consultant numbers vary over time and by clinical specialty. This is influenced by the value invested in the role by local nursing leadership and by national policy change. A lack of role clarity affects the uptake and sustainability of advanced practice roles internationally and is also an issue for the nurse consultant role in England's mental health services. What are the implications for practice?: Successfully introducing advanced practice nursing roles in mental health services requires role clarity and support from local nurse directors. The continued absence of robust evidence as to the clinical/cost‐effectiveness of nurse consultant roles in mental health settings places an onus on individual posts to generate data to justify the role at a time of financial constraint. Detailed post holder characteristics reported in this paper provide a basis for future comparison with other advanced practice roles in mental health services and other specialties nationally and internationally. Abstract: Introduction: The nurse consultant is an advanced practice role providing expert clinical practice, consultancy and professional leadership. To date, few studies have examined this role within mental health services and none have described the professional characteristics of post holders. Aims: The main aims of the study were to identify changes in nurse consultant numbers in mental health services, identify post holder characteristics and factors influencing number of posts. Method: We used a triangulated mixed methods approach comprised of a longitudinal examination of national workforce data, a national cross‐sectional survey of post holder characteristics and semi‐structured interviews with directors of nursing. Results: Of 58 mental health organizations, 51 (88%) responded, identifying 123 nurse consultant posts, and a range of 0–12 posts per organization. One in 229 mental health nurses and 1 in 186 learning disability nurses were nurse consultant. An average of 40% of nurse consultants' work time was reported as being in clinical practice. Themes identified as important in relation to role sustainability were cost and value, contribution of individual post holders, role clarity and domains of work. Discussion: Nurse consultants are represented to a greater extent in the mental health service workforce than in nursing generally, but their roles often lack clarity. Attitudes of local professional leaders and national policies are likely to affect post numbers. Implications for practice: Developing and sustaining nurse consultant roles requires role clarity and active support from nurse leaders. Roles need to demonstrate their value to the clinical systems in which they work.